The natural distribution, growth and botanical variation of Pinus caribaea and its cultivation in South Africa - Lückhoff, H. A.(Hilmar Albert) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc. (Forestry)) -- University of Stellenbosch, 1964.